Mechanical and thermal properties of potassium salts of poly(ethylene‐co‐ethylacrylate): Polyolefin ionomers in the absence of acid groups. Issue 8 (18th October 2014) - Aoyama, Masataka; Koda, Tomonori; Miyata, Ken; Nishio, Taichi; Nishioka, Akihiro
<x xml:space="preserve">Abstract</x> The thermal and mechanical properties of ionomers prepared by partial saponification of poly(ethylene‐co‐ethylacrylate) (EEA) with potassium were investigated by using differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA). The Vicat softening temperature (VST) and bending modulus were also evaluated. Molecular design of the present EEA‐based ionomers eliminates acid groups, which affect ionic aggregates for conventional ionomers. The DSC results showed that the melting enthalpy and main crystallization temperature decreased as the ion content increased, whereas on the other hand, the crystal melting temperature at about 360 K did not depend on the ion content, and a secondary exothermal peak was observed in the cooling process. The variance of the VST increased as the crystallinity decreased. The temperature‐dependent curves of DMA data of the EEA‐based potassium ionomers with a higher ion content showed elastic plateau even at temperatures above their crystal melting points. Our results indicate the existence of strong cross‐linking mediated by ion aggregates. The quadratic increase of stiffness as a function of ion content, increasing VST with decreasing crystallinity, and elastic plateau of temperature‐dependent moduli above crystal melting temperature are significant characteristics of the EEA‐based potassium ionomers, which contain ionic aggregations without acid group presence. POLYM. ENG. SCI., 55:1843–1848, 2015. © 2014 Society of Plastics Engineers